2010
DOI: 10.1016/j.breast.2010.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral prophylactic mastectomy in women with inherited risk of breast cancer – Prevalence of pain and discomfort, impact on sexuality, quality of life and feelings of regret two years after surgery

Abstract: It is important to inform women approaching this prophylactic procedure about the risk of having unwanted secondary effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
70
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(79 citation statements)
references
References 45 publications
4
70
0
5
Order By: Relevance
“…Despite the difficulties in sexual function and increased menopausal symptoms following RRSO, the level of regret was low in this sample, and this supports the hypothesis that reductions in perceived risk and cancer-related anxiety outweigh any regret related to adverse outcomes [15]. Nevertheless, the findings of this study support the need to foster realistic expectations about potential sexual dysfunction and menopausal symptoms in women considering RRSO.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Despite the difficulties in sexual function and increased menopausal symptoms following RRSO, the level of regret was low in this sample, and this supports the hypothesis that reductions in perceived risk and cancer-related anxiety outweigh any regret related to adverse outcomes [15]. Nevertheless, the findings of this study support the need to foster realistic expectations about potential sexual dysfunction and menopausal symptoms in women considering RRSO.…”
Section: Discussionsupporting
confidence: 70%
“…Early studies found no evidence of a negative sexual impact in 79 women who opted for RRM up to 18 months post-surgery [19] and only minor deteriorations in body image in 76 women who had RRM up to three years prior [20]. In contrast, Brandberg et al [21] reported significant reductions in body image and sexual pleasure in 90 unaffected women one year after RRM, and more recent findings suggest these negative impacts continue at least up to two years following RRM [15,22].…”
Section: Introductionmentioning
confidence: 97%
“…A majority reported high overall satisfaction with the cosmetic results six months and one year after BRRM, corresponding to their expectations (12). At 2-years follow up, a majority reported pain and discomfort in the breasts, as well as reduced sexual sensations (13,14). Finally, the prospective 2-years follow-up of women with breast cancer who had CRRM showed no adverse effects on HRQoL, emotional distress or sexuality, but some aspects of body image were affected negatively (15).…”
Section: Introductionmentioning
confidence: 67%
“…A collaborative group, consisting of geneticists, oncologists, breast surgeons, plastic surgeons, nurses and a psychologist, was established at the Karolinska University Hospital in 1996 in order to meet the increasing interest in RRM in women at high hereditary risk. A prospective questionnaire study of the expectations on RRM, satisfaction with the result of RRM, emotional reactions, body image, sexuality and HRQoL were conducted, including women who underwent RRM between 1997 and 2010, and the results have been published in a number of papers (4,(10)(11)(12)(13)(14)(15). In conclusion, the results showed that unaffected women, opting for bilateral RRM, reported similar HRQoL levels as a normative population, whereas patients opting for contralateral RRM were comparable to breast cancer patients (10).…”
Section: Introductionmentioning
confidence: 99%
“…The intensity of acute postoperative pain is a good predictor of long-term pain; however, adequate control of acute postoperative pain does not always lead to a decrease in the incidence of developing long term pain (Perkins and Kehlet, 2000). To reduce the level of tissue injury during surgery, surgical procedures have been modified including those used for joint repair (Kehlet et al, 2006); mastectomy and breast reconstruction (Gahm et al;Vadivelu et al, 2008) and herniorraphy (Nathan and Pappas, 2003;Pokorny et al, 2008); however, a significant percentage of patients still develop chronic pain. Hence, there is a need to develop treatments that can be used before and during the early phases following nerve injury (as a result of surgery or trauma) to prevent the development of chronic pain.…”
Section: Introductionmentioning
confidence: 99%